Pengaruh Fasilitas Belajar di Rumah Terhadap Prestasi Belajar Siswa Sekolah Menengah Atas - Siti Raodha Muttalib; Radjab Mansyur; M. Ramli AT (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
Learning facilties at home are all kinds of facilities and infrastructure available in the home that can support or assist in the learning process. Learning facilities and infrastructure must be planned and managed properly so that the learning process can help students learn.  The research aims at analyzing the effect of learning facilities at home on the learning achievements at the State Senior High School 1 Campalagian, Polewali Mandar Regency. This was quantitative research with the survey method, the research data was examined using the simple linear regression test. The result showed that the learning facilities at home owned by male and female students were categorized as adequate in helping the learning process at home. In addition, male and female students prefer learning furniture as a facility that must always be used in the learning process at home. The research result indicates that there is no significant effect between the learning facilities at home and leraning achievement of the male and female students.